Islamic Education and Religiosity: Voices of the Indonesian Muslim Communities in Australia - Teuku Zulfikar; Emawati Emawati (Universitas Islam Negeri Mataram, 2020)
Indonesian Muslims have made their presence in Australia since the 1970s. Some of them now have become citizens and others preferred to be permanent residents. As they have lived in Australia, in which Islam is not the dominant religion, they were concerned with their children’s religiosity. These Muslims attempted to teach Islam to their children in any way possible. This research, therefore aims at exploring Indonesian Muslims’ parents’ ways of teaching Islam to their children, and their children’s responses on their parents’ approaches in educating them Islam. Using in-depth interviews, the study unveiled that the parents used various aproaches. Their approaches were democratic, in which a great deal of dialogues and neggotiation took place. They also monitored their children’s attitudes and kept reminding them about Islam; setting the role models was also a significant approach used in teaching Islam to their children, and balancing the public schooling and the madrasah. The findings also revealed that these young Muslims recognized the significant role their parents have taken to teach them Islam and shape their religiosity and they were thankful for their parents although some dissenting views on several issues also emerged.